The Role of Tumor Necrosis Factor  (TNF ) and Matrix Metalloproteinase9 (MMP9) Serum in Preterm Premature Rupture of Membranes - Ardiles, Ardiles; Desmiwarti, Desmiwarti; Bachtiar, Hafni (Indonesian Socety of Obstetrics and Gynecology, 2017)
Objective: To investigate the role of TNF- and MMP-9 serum in preterm premature rupture of membranes (PPROM). Methods: We used cross-sectional study design. Subjects were all pregnant women with and without PPROM who underwent checkup at Obstetrics and Gynecology Functional Medical Staff General Hospital Dr. M. Djamil and networking hospital. Results: A total of 48 subjects were enrolled in this study. The mean serum levels of TNF- in patients with PPROM 17.43 ng/ml  12.4 ng/ml and without PPROM 8.45 ng/ml  6.86 ng/ml. The mean serum levels of MMP-9 in patients with PPROM 8.77 ng/ml  4.41 ng/ml, and without PPROM 4.46 ng/ml  3.04 ng/ml. Statistical test result p value <0.05, it can be conclude there are differences in the levels of TNF- and MMP-9 serum in premature rupture of membranes and without premature rupture of membranes pregnancy of preterm. Conclusion: There are differences in the levels of TNF- and MMP-9 serum in PPROM and without PPROM.Keywords: MMP-9, premature rupture of membranes, TNF-